A single EGF-like motif of laminin is responsible for high affinity nidogen binding. - Mayer, U (1993)
A major nidogen binding site of mouse laminin was previously localized to about three EGF-like repeats (Nos 3-5) of its B2 chain domain III [M. Gerl et al. (1991) Eur. J. Biochem., 202, 167]. The corresponding cDNA was amplified by polymerase chain reaction and inserted into a eukaryotic expression vector tagged with a signal peptide. Stably transfected human kidney cell clones were shown to process and secrete the resulting fragment B2III3-5 in substantial quantities. It possessed high binding activity for recombinant nidogen in ligand assays, with an affinity comparable with that of authentic laminin fragments. In addition, complexes of B2III3-5 and nidogen could be efficiently converted into a covalent complex by cross-linking reagents. Proteolytic degradation of the covalent complex demonstrated the association of B2III3-5 with a approximately 80 residue segment of nidogen domain G3 to which laminin binding has previously been attributed. The correct formation of most of the 12 disulfide bridges in B2III3-5 was indicated from its protease resistance and the complete loss of cross-reacting epitopes as well as of nidogen-binding activity after reduction and alkylation. Smaller fragments were prepared by the same recombinant procedure and showed that combinations of EGF-like repeats 3-4 and 4-5 and the single repeat 4 but not repeats 3 or 5 possess full nidogen-binding activity. This identifies repeat 4 as the only binding structure. The sequence of repeat 4 is well conserved in the human and in part in the Drosophila laminin B2 chain.(ABSTRACT TRUNCATED AT 250 WORDS)